KENDALA GURU DALAM PENGGUNAAN APLIKASI RUANG GTK DI SEKOLAH DASAR - Ismawanti, Afifah; Sastrawati, Eka; Alirmansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the obstacles faced by teachers in using the Teacher and Education Personnel (GTK) Space application in elementary schools. Using a descriptive qualitative approach, the research was conducted at SD Negeri 55/I Sridadi involving 10 teachers as respondents through in-depth interviews and participatory observation techniques. The results identify multidimensional obstacles including limitations in teachers’ digital literacy, operational complexity of the application, technological infrastructure distruptions, demographic factors of teacher age, and limitations in support and mentoring systems. These obstacles impact teachers’ time management and workload, creating an efficiency paradox where technology designed to enhance productivity actually generates additional administrative burden. Despite facing various challenges, teachers acknowledge significant benefits in the form of centralized data managementand improved accessibility to personnel information. The variation in teacher responses shows a diverse spectrum of adaptation, from resistance to enthusiastic adoption, influenced by internal and external factors. The study recommends implementing comprehensive strategies including continuous training programs with differentitation approaches, establishment of robust support systems, strengthening institutional support, and improving application user interface to optimize the utilization of digital technology in supporting teacher professionalism and learning quality in elementary school.